THE HIERARCHY OF NEEDS REFLECTED IN MICHAEL OHER’S CHARACTER IN THE BLIND SIDE MOVIE - Sari, Linda; Natsir, M.; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
ABSTRACT This study is aimed to find how Michael Oher fulfilled his needs and to convey Michael Oher’s character when all his needs have been fulfilled and his dominant character in the movie of The Blind Side. The method that is used by the writer is descriptive qualitative. The data of this study were analyzed with the hierarchy of needs theory by Abraham Maslow. The writer analyzed the dialogue also narration that reflected the needs of the main character and also the changes of his character. The result of this study shows Oher could fulfill all of his needs from the lowest stage that begins with physiological needs, safety needs, love and belonging needs, self-esteem needs, and the last is self-actualization needs. Regarding to all of his needs that had been already fulfilled, his character also changed from a silent boy to a confident character who could express himself in sport and became one of the players that had a big influenced to the team. Last, for the dominant character that appeared in Oher was the protective character which was found in two different needs based on Maslow’s. Keywords: hierarchy of needs, character, characterization, The Blind Side movie  ABSTRAK Kajian ini bertujuan untuk mengetahui bagaimana Michael Oher memenuhi kebutuhan hidupnya dan menemukan bagaimana karakter Michael Oher ketika segala kebutuhan hidupnya sudah terpenuhi. Juga, kajian ini bertujuan untuk mengungkap karakternya yang dominan. Metode yang digunakan penulis adalah deskriptif kualitatif. Data penelitian ini dianalisa dengan teori Hierarchy of Needs dari Abraham Maslow. Penulis menganalisa dialog dan juga narasi yang mencerminkan kebutuhan hidup karakter utama dan perubahan karakternya. Hasil dari penelitian ini menunjukan bahwa Oher mampu  memenuhi kebutuhan mulai dari kebutuhan fisiologis, kemanan, sosial, harga diri, dan kebutuhan pencapaian. Berkaitan dengan semua kebutuhan yang sudah terpenuhi, karakternya juga berubah dari lelaki yang pendiam menjadi karakter yang percaya diri dan bisa mengekspresikan dirinya dalam olahraga dan juga menjadi salah satu pemain yang memiliki pengaruh besar bagi timnya. Terakhir, untuk karakter dominan yang terlihat di Oher adalah karakter yang protektif dan di temukan didalam dua kebutuhan berbeda berdasarkan teori dari Maslow.  Kata kunci: hierarchy of needs, karakter, pemeranan, film The Blind Side